Towards culturally inclusive mental health: learning from focus groups with those with refugee and asylum seeker status in Plymouth. Issue 4 (10th December 2018) - Fish, Matthew; Fakoussa, Olivia
Abstract : Purpose: Pre- and post-immigration trauma and stress make refugees a particularly vulnerable group in terms of mental health and well-being. The purpose of this paper is to describe a listening project undertaken in Plymouth, UK, which sought the views of 17 service users ( n =12) and staff ( n =5) from four local support organisations, for people with refugee and asylum seeker status and those with diverse cultural backgrounds. Aims of the project were to expand Western-centric understandings regarding beneficial support and the promotion of good mental health and well-being in this population. Design/methodology/approach: Responses were subjected to thematic analysis, co-conducted with a service user. Participants were asked about their personal understandings of mental health and well-being and what supports or hinders well-being. Findings: The findings enabled the development of a model incorporating 10 threads which support and 9 holes that can hinder well-being. Research limitations/implications: The relatively small numbers of participants compared with the numbers of asylum seekers and refugees in Plymouth may not be fully representative of the general population in Plymouth and the UK. Originality/value: Despite increasing cultural diversity within the UK population, available mental health services exist mainly as developed from a Western psychological model of mental distress and treatment. This research provides services with a more informed understanding of mental health for asylum seekers and refugees. As such it is of value towards future service design in Plymouth and the UK. Findings also contributed to a successful funding bid to set up a peer-led support project in the city.